A rubber composition for tire crown components and preparation method thereof

By using a specific formula rubber composition in the tire material, combining components such as hydrazide compounds and silane coupling agents, a complex network structure is formed, which solves the problem of insufficient fatigue resistance under low rolling resistance, and achieves both high damage resistance, low hysteresis loss and low heat generation.

CN119751999APending Publication Date: 2025-04-04OTSUKA MATERIAL SCI & TECH SHANGHAICO LTD

Patent Information

Application Number
CN202510047882.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

With the demand for low rolling resistance, existing tire materials are difficult to maintain high fatigue crack resistance, low hysteresis loss and low thermal performance at the same time.

Method used

A rubber composition containing components such as diene rubber, hydrazide compound, reinforcement filler, low roll resistance modifier, silane coupling agent, etc. is adopted, and a complex network structure is formed to improve fatigue resistance through specific mixing and vulcanization treatment methods.

Benefits of technology

The anti-destructive performance of the rubber composition is significantly improved, crack initiation and expansion is delayed, physical properties retention rate after aging is improved, while maintaining low hysteresis loss, low heat generation and low rolling resistance performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239054440000041
    Figure BDA0005239054440000041
  • Figure BDA0005239054440000091
    Figure BDA0005239054440000091
  • Figure BDA0005239054440000101
    Figure BDA0005239054440000101
Patent Text Reader

Abstract

The invention discloses a rubber composition for tire crown components, specifically related to the field of rubber, including the following raw materials by weight: 100 parts of diene rubber, 0.3-3 parts of hydrazide compounds, 40-160 parts of reinforcing fillers, 0-1.5 parts of low rolling resistance modifiers, 2-18 parts of silane coupling agents, vulcanization accelerators, vulcanizing agents, antioxidants, vulcanization activators, processing aids, resins and plasticizers. Hydrazide compounds can improve the compatibility between rubbers, and after complexing with zinc oxide, stabilize sulfur cross-linking bonds, thereby improving fatigue crack resistance, delaying crack initiation, reducing crack propagation rate, and improving physical property retention after aging. Low rolling resistance modifiers can react with the double bonds of synthetic diene rubbers in a trans-Diels-Alder reaction, which has the effect of reducing rolling resistance. Hydrazide compounds and low rolling resistance modifiers are used together, and the rubber composition has the performance of anti-fatigue, anti-crack growth, anti-collapse and block falling, low hysteresis loss, low heat generation, and low rolling resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tire manufacturing, and more particularly to a rubber composition used in a tire crown component and a preparation method thereof. Background Art

[0002] At present, with the development of automobile industry, passenger cars have become an indispensable means of transportation in people's lives. Tires are very important parts of cars, and they are the only parts of cars that are in contact with the ground. Various performances of cars, such as driving and braking performance, fuel economy performance, ride comfort performance, handling stability performance, anti-destruction performance, safety performance, etc., are completely achieved by the interaction between tires and the ground. The quality of tire performance is extremely important to cars.

[0003] Rubber materials are prone to fatigue under external cyclic stress, which reduces the mechanical properties of the material, initiates cracks, further expands the cracks, and finally destroys the material. Driven by EU labeling laws, vehicle electrification, and environmental protection, tire technicians must develop tires with lower rolling resistance. The application of modified styrene-butadiene rubber, new silane coupling agents, and lightweight tires has reduced the anti-destruction performance of tires. At the same time, the increase in ozone concentrations worldwide has also aggravated cracking on the tire surface. Problems such as tire tread cracks and groove bottom cracks frequently occur, causing people to worry about the service life and safety of tires.

[0004] In order to improve the fatigue performance of tires, people have studied the failure mechanism of materials. It is generally believed that the fatigue process of materials can be divided into two parts: crack initiation and crack propagation, and different rubbers have different manifestations. Taking natural rubber (NR) and butadiene rubber (BR) as examples, BR has a higher ability to resist crack formation, that is, crack initiation is slow; and when cracks occur, the NR system has a lower crack propagation rate. Therefore, when designing the formula, the performance of various materials needs to be considered comprehensively. In addition to a large amount of rubber materials, the tire formula also uses inorganic fillers, plasticizers, antioxidants, vulcanizers and other materials. The uniformity of the system and the number of inherent defects play an important role in tire fatigue.

[0005] Changing the type of rubber or adjusting the amount of white carbon black and carbon black used through traditional technology often results in performance limitations. Since low rolling resistance requires the rubber material to have lower energy dissipation (hysteresis loss), while fatigue crack resistance requires higher energy dissipation capacity, low rolling resistance and fatigue crack resistance are contradictory. While reducing rolling resistance, fatigue crack resistance (crack initiation, expansion and growth) often deteriorates, and often when improving one performance, it is accompanied by the loss of other performances, which makes it difficult to improve the fatigue crack resistance of low rolling resistance tires. Therefore, it is currently difficult to achieve improvements in both low rolling resistance and fatigue crack resistance.

[0006] In the prior art, patent publication number CN102257056A discloses a composition based on natural rubber and a reinforced inorganic filler containing dihydrazide, which improves the hysteresis to a certain extent. However, it can be seen from the content of the patent that the improvement of the hysteresis is relatively low, and there is still room for improvement, and there is no description and example data description for the fatigue crack resistance performance. Therefore, in view of the contradiction between low heat generation and low rolling resistance and fatigue crack resistance performance, the rubber composition cannot meet the use requirements of low rolling resistance of tires and improve fatigue crack resistance at the same time.

[0007] Patent publication number CN103261300A discloses a rubber composition with a carbon black content greater than 50%, which is a highly dispersed low heat generation composition obtained by mixing natural rubber and carbon black by a liquid phase method and adding a dihydrazide compound, but there is no description and example data description of fatigue crack resistance. Therefore, in view of the contradiction between low heat generation and low rolling resistance and fatigue crack resistance, the rubber composition cannot meet the use requirements of low rolling resistance of tires and improve fatigue crack resistance at the same time.

[0008] Patent publication number CN111592695A discloses a rubber composition composed of natural rubber with low rolling resistance additive 1-naphthylacetylhydrazine and high cis-butadiene rubber or 0-40 parts of solution-polymerized butadiene styrene, fillers, additives, etc., mainly for the purpose of obtaining low rolling resistance or low hysteresis without affecting wear performance, but there is no description and example data description for fatigue crack resistance. Therefore, in view of the contradiction between low heat generation and low rolling resistance and fatigue crack resistance, the rubber composition cannot meet the use requirements of low rolling resistance of tires and improve fatigue crack resistance at the same time.

[0009] The invention patent with patent application publication number CN113652012A discloses a low heat generation and high thermal conductivity tire base rubber composition, its mixing method and tire. The invention adopts a large amount of thermal conductive fillers to reduce heat generation and improve thermal conductivity, and adopts carbon black dispersant to reduce the interaction between fillers to reduce heat generation. The prepared base rubber composition has the characteristics of low heat generation and high thermal conductivity, improves the crown heat generation and thermal conductivity problems during tire driving, reduces fuel consumption, and increases the service life of the tire.

[0010] The invention patent with patent application publication number CN104558713A discloses a rubber composition having low heat generation performance and adhesiveness, and can improve the durability of a pneumatic tire.

[0011] In summary, in the prior art, solution-polymerized styrene-butadiene rubber and new silane coupling agents are used to reduce rolling resistance, but their fatigue crack resistance and damage resistance are often affected. Rolling resistance can be reduced by adjusting the tire structure, such as reducing weight and adjusting the tire width, but this will reduce grip, limit road adaptability, and weaken handling capabilities.

[0012] Therefore, how to provide a rubber composition for manufacturing tires and a preparation method thereof that has high anti-destructive performance, reduces crack propagation rate, delays crack initiation, improves aging property retention rate, and has low hysteresis loss, low heat generation, and low rolling resistance performance is a problem that technical personnel in this field urgently need to solve. Summary of the invention

[0013] In order to overcome the above defects of the prior art, the present invention provides a rubber composition for a tire crown component and a preparation method thereof to solve the problems raised in the above background technology.

[0014] To achieve the above object, the present invention provides the following technical solution: a rubber composition for a tire crown component, comprising the following raw materials in parts by weight: 100 parts of diene rubber, 0.3-3 parts of hydrazide compound, 40-160 parts of reinforcing filler, 0-1.5 parts of low rolling resistance modifier, 2-18 parts of silane coupling agent, 0.1-4.5 parts of vulcanization accelerator, 0.1-4.5 parts of vulcanizing agent, 1-6 parts of antioxidant, 0.1-5 parts of vulcanization activator, 0-5 parts of processing aid, and 0-80 parts of resin and plasticizer;

[0015] Preferably, the hydrazide compound structure is:

[0016] R1-CO-NH-NH2(1)

[0017] NH2-NH-CO-R2-CO-NH-NH2(2)

[0018] R3-CO-NH-N=R4 (3)

[0019] Wherein, R1, R2, R3, and R4 are independently selected from: an aromatic hydrocarbon group having 6 to 30 carbon atoms or an alkane group having 6 to 30 carbon atoms; the aromatic hydrocarbon is arbitrarily substituted by an alkyl group, a hydroxyl group, or an amino group having 1 to 20 carbon atoms.

[0020] The low rolling resistance modifier has a structure of:

[0021]

[0022] Wherein X1 and X2 represent a heterocyclic group which may have a substituent, and the substituent is an alkyl group, an aralkyl group, an aryl group or a heterocyclic group.

[0023] Preferably, the diene rubber is any one or more combinations of modified or unmodified natural rubber, polyisoprene rubber, polybutadiene rubber, butadiene rubber, styrene-butadiene copolymer rubber, ethylene-propylene-diene monomer copolymer, styrene-isoprene-styrene terblock copolymer rubber, and styrene-butadiene-styrene terblock copolymer rubber.

[0024] Further preferably, the diene rubber is a combination of any one or more of modified or unmodified styrene-butadiene copolymer rubber and polybutadiene rubber, and the amount of the styrene-butadiene copolymer rubber and polybutadiene rubber is 50-100 parts.

[0025] Further preferably, the diene rubber is a combination of any one or more of modified or unmodified natural rubber and polyisoprene rubber, and the amount of the natural rubber and polyisoprene rubber is 0-50 parts.

[0026] Preferably, the hydrazide compound is a combination of any one or more of adipic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, suberic acid dihydrazide, sebacic acid dihydrazide, dodecanoic acid dihydrazide, benzoic acid hydrazide, naphthoic acid hydrazide, propionic acid hydrazide, caprylic acid hydrazide, stearic acid hydrazide, caproic acid hydrazide, capric acid hydrazide, oleic acid hydrazide, lauric acid hydrazide, palmitic acid hydrazide, N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide, 2-hydroxy-naphthoic acid hydrazide, 3-hydroxy-2-naphthoic acid hydrazide, and 2-hydroxy-benzoic acid hydrazide, and the amount of the hydrazide compound is 0.3-1.5 parts, and more preferably 0.3-1.2 parts.

[0027] More preferably, the hydrazide compound is (N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide.

[0028] Preferably, the low rolling resistance modifier is a tetrazine compound, and further, the low rolling resistance modifier is a combination of any one or more of 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine, 3,6-bis(3-pyridyl)-1,2,4,5-tetrazine, and 3,6-bis(4-pyridyl)-1,2,4,5-tetrazine, and the amount of the low rolling resistance modifier is 0.3-1.5 parts, and more preferably 0.3-1.2 parts.

[0029] More preferably, the low rolling resistance modifier is preferably 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine.

[0030] In the present invention, by adding hydrazide compounds to the rubber composition, the anti-destruction performance of the rubber composition can be improved, crack initiation is delayed, crack propagation rate is reduced, and the physical property retention rate of the rubber composition after aging is improved. The rubber composition has the performance of low hysteresis loss, low heat generation and low rolling resistance. In particular, after adding 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine, the rubber composition has lower rolling resistance performance.

[0031] Preferably, the reinforcing filler is a mixture of one or more of modified or unmodified carbon black, acetylene black, white carbon black, carbon nanotubes, graphite, and graphene, and the amount of white carbon black in the reinforcing filler is 40-150 parts, and the amount of carbon black is 1-40 parts.

[0032] Furthermore, the amount of white carbon black is preferably 40-120 parts, and more preferably 50-100 parts.

[0033] Furthermore, the amount of carbon black is preferably 1-35 parts, and more preferably 4-30 parts.

[0034] The specific surface area of ​​the carbon black is 20-160m 2 / g, the specific surface area of ​​white carbon is 60-250m 2 More preferably, the specific surface area of ​​the carbon black is 40-140m 2 / g, the specific surface area of ​​white carbon is 90-230m 2 / g.

[0035] More preferably, the carbon black is one or a combination of N110, N121, N134, N220, N231, N234, N242, N293, N299, N315, N326, N330, N332, N339, N343, N347, N351, N358, N375, N539, N550, N582, N630, N642, N650, N683, N754, N762, N765, N774, N787, N907, N908, N990 and N991; the iodine absorption value of the above carbon black is 5-150g / kg, and the DBP absorption value is 30-150cm 3 / 100g.

[0036] Preferably, the coupling agent is a combination of any one or more of bis-[3-(triethoxysilyl)propyl]-tetrasulfide, bis-[3-(triethoxysilyl)propyl]-disulfide, 3-octanoylthio-1-propyltriethoxysilane, γ-mercaptopropylethoxybis-(propyl-hexaethoxysiloxane) and mercaptoalkoxy-ethoxy or methoxysilane, and the coupling agent is used in an amount of 3-16 parts.

[0037] Preferably, the following raw materials are also included in parts by weight: 1-6 parts of antioxidant, 0.2-5 parts of stearic acid, 1-9 parts of zinc oxide, 0.5-5 parts of protective wax, 0-5 parts of processing aid, 2-80 parts of plasticizer, 0.1-4.5 parts of sulfur, and 0.1-4.5 parts of vulcanization accelerator.

[0038] Preferably, the plasticizer composition includes processing oil and / or resin. The plasticizer can be added during the rubber mixing process or contained in the rubber. The plasticizer includes one or a combination of aromatic oil, environmentally friendly aromatic oil, cycloalkane oil, paraffin oil, MES, TDAE, plant oil, etc., and can also include various resins, such as petroleum resin, terpene resin, limonene resin, DCPD dicyclopentadiene resin, etc.

[0039] Preferably, the processing aid is a fatty acid, a metal fatty acid salt, a fatty acid ester, a condensation product of a fatty acid and a high molecular fatty acid ester, and a mixture thereof with soaps.

[0040] Preferably, the vulcanization accelerator is any one of thiazoles, thiurams, sulfenamides, dithiocarbamates, xanthates, guanidines and thioureas, or a combination of several of them.

[0041] The rubber composition for a tire crown component, and its preparation method, comprises the following steps:

[0042] Step (1) weighing various raw materials: the raw materials include diene rubber, hydrazide compound, reinforcing filler, low rolling resistance modifier, silane coupling agent, vulcanization accelerator, vulcanizing agent, antioxidant, vulcanization activator, processing aid, resin and plasticizer, stearic acid, zinc oxide, protective wax and sulfur;

[0043] Step (2) mixing diene rubber and hydrazide compound, low rolling resistance modifier, antioxidant, silane coupling agent, processing aid, etc. for 30-200 seconds, mixing reinforcing filler, silane coupling agent and plasticizer and reacting at 80-160° C. for 30-200 seconds, adding vulcanization activator at 80-140° C. and mixing at 120-180° C. for 60-300 seconds, and cooling to obtain material A;

[0044] Step (3) adding a vulcanizing agent and a vulcanization accelerator to material A, mixing and discharging the mixture, and then subjecting the mixture to a vulcanization reaction at a temperature of 130-180° C. and a vulcanization time of 10-200 min, to obtain a rubber composition for a tire crown component.

[0045] Furthermore, in step (2), the mixing time is 2-10 min, and the discharge temperature is 120-180°C.

[0046] A tire, the crown component of the tire is prepared from the rubber composition used in the crown component of the tire.

[0047] The rubber composition for a tire crown component and the preparation method thereof provided by the present invention have the following beneficial effects:

[0048] The present invention can improve the anti-destruction performance, reduce the crack propagation rate, and increase the retention rate of physical properties after aging by adding a small amount of hydrazide compounds. Hydrazide compounds form a complex network with zinc oxide, that is, in addition to forming the cross-linking bonds of the rubber system, they also form a weak complex network structure. When subjected to external force, they can be preferentially broken as sacrificial bonds, absorbing part of the destructive energy, thereby improving the fatigue crack resistance of the rubber composition. In particular, the addition of 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine makes the crown component of the tire made of the composition have lower rolling resistance performance; the preparation method of the present invention is simple to operate and highly practical. DETAILED DESCRIPTION

[0049] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0050] The standards and methods for testing the rubber composition of the present invention in the following examples are as follows:

[0051] 1) Mooney viscosity: refer to ASTM D1646-2007, the test condition is ML (1+4) 100°C. The larger the index, the higher the Mooney viscosity.

[0052] 2) Mooney scorch: Refer to ASTM D1646-2007, the test temperature is 130 degrees Celsius. The larger the index, the longer the scorch time.

[0053] 3) Hardness: Shore hardness test, refer to ASTM D2240-2010. The larger the index, the higher the hardness.

[0054] 4) MA100: 100% tensile modulus test, refer to ASTM D412-2006, take the modulus when the elongation is 100%, the test environment temperature is 23±2°C. The larger the index, the higher the tensile modulus.

[0055] 5) MA300: 300% tensile modulus test, refer to ASTM D412-2006, take the modulus when the elongation is 300%, the test environment temperature is 23±2°C. The larger the index, the higher the tensile modulus.

[0056] 6) Tensile strength and elongation at break: refer to ASTM D412-2006, the sample is dumbbell-shaped, the test speed is 500mm / min, and the test environment temperature is 23±2°C. The larger the index, the higher the tensile strength.

[0057] 7) Tear strength: refer to ASTM D624-2007, use right-angle specimen, test speed 500mm / min, test environment temperature 23±2℃. The larger the index, the higher the tear strength.

[0058] 8) Hysteresis loss factor: Tested using Metravib DMA, temperature 25°C, frequency 10 Hz, dynamic deformation 0.07%-50%, plane shear mode. The smaller the index, the smaller the hysteresis loss.

[0059] 9) Tensile fatigue: Refer to ISO6943:2007 and use a multi-station microcomputer rubber tensile fatigue testing machine to test. When the tensile fracture occurs, the more tensile times, the better the fatigue performance; or the more tensile fatigue times a group of specimens breaks when 50% of them break, the better the tensile fatigue performance.

[0060] 10) Crack growth rate: Refer to ISO27727:2008 and use a crack growth tester to test. The lower the crack growth rate, the better the ability to resist crack growth.

[0061] The raw materials used in the embodiments of the present invention are as follows:

[0062] SOL5251H (styrene-butadiene rubber): Kumho Petrochemical Company, South Korea

[0063] BR9000 (polybutadiene rubber): Sinopec Qilu Petrochemical Company

[0064] Natural rubber: No. 20 standard rubber, Sinochem International (Holdings) Co., Ltd.

[0065] Multifunctional modifier: N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide, Otsuka Chemical Co., Ltd.

[0066] Low rolling resistance modifier: 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine, Otsuka Chemical Co., Ltd.

[0067] 3-Hydroxy-2-naphthoylhydrazide: Exploration Platform Toluene dicarboxylic acid dihydrazide: TCI (Shanghai) Chemical Industry Development Co., Ltd. HD165MP (white carbon black): Wuxi Quecheng Silicon Co., Ltd.

[0068] N234.N375: Cabot Carbon Black

[0069] Si69: Nanjing Shuguang Chemical Group Co., Ltd.

[0070] X50S: Evonik Chemicals

[0071] Si75: Jiangxi Chenguang New Materials Co., Ltd.

[0072] 6PPD (antioxidant): Shandong Shangshun Chemical Co., Ltd. Protective wax: Antilux 111, Lanxess Chemical, Germany

[0073] Vivatec 700 (environmentally friendly aromatic oil): Germany Hansheng Co., Ltd.

[0074] HB103 (hydrogenated DCPD dicyclopentadiene petroleum resin): Japan JXTG Co., Ltd. Stearic acid: Sichuan Tianyu Oil Chemical Co., Ltd.

[0075] Zinc Oxide: Dalian Zinc Oxide Co., Ltd.

[0076] DPG (diphenylguanidine): Shandong Shangshun Chemical Co., Ltd.

[0077] CBS (N-cyclohexane-2-benzothiazole sulfenamide): Shandong Shangshun Chemical Co., Ltd. Sulfur: Shandong Shangshun Chemical Co., Ltd.

[0078] Example 1

[0079] The raw materials of the rubber composition are as follows in Table 1:

[0080] Table 1 Comparative Examples 1-1 to 1-3 and Examples 1-1 to 1-5 Formulations

[0081]

[0082]

[0083] The raw materials used in Comparative Examples 1-1 to 1-3 and Examples 1-1 to 1-4 of the present invention are shown in Table 1, all in mass parts. Among them, Examples 1-1 to 1-5 are rubber compositions using N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide and 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine alone or in combination.

[0084] Preparation method of the rubber composition in Table 1: (1) Weigh each raw material according to the weight proportion of the rubber composition in Table 1; (2) SOL5251H, BR9000 and natural rubber are mixed for 30 seconds, hydrazide compounds, tetrazine compounds, protective wax, stearic acid, 6PPD, DPG and Si69 are added and mixed for 90 seconds, HD165MP, N234 and Vivatec700 are added and mixed, zinc oxide is added and mixed at 135°C, the mixing time is 120 seconds at a temperature of 140-150°C, and the debonding temperature is 150°C to obtain material A; (3) Material A is left for 4 hours, cooled, sulfur and CBS are added and mixed, the mixing is performed for 180 seconds, and the debonding temperature is 105°C to obtain the rubber composition.

[0085] The performance test results for Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 are shown in Table 2 below:

[0086] Table 2: Comparison of performance results of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3

[0087]

[0088] * The test results of the rubber composition are expressed in the form of an index, with the test result of Comparative Example 1-1 being 100.

[0089] The calculation formula is: Example test result = (Example / Comparative Example 1-1)×100.

[0090] a Crack Growth Rate Index @2000J / m 2 :Evaluated by crack extension tester, the data in Table 2 are tearing energy 2000J / m 2 The smaller the exponent, the slower the crack growth rate.

[0091] b1 Tensile strength after aging, b2 Elongation at break after aging: aging temperature is 100℃, aging time is 72 hours, thermal oxygen aging.

[0092] b3 Tensile strength aging retention rate = tensile strength after aging / tensile strength before aging. The larger the value, the higher the tensile strength aging retention rate.

[0093] b4 Elongation at break aging retention rate = elongation at break after aging / elongation at break before aging. The larger the value, the higher the elongation at break aging retention rate.

[0094] c Tensile fatigue index: evaluated by a tensile fatigue testing machine. The data in Table 4 are the tensile fatigue times when the sample breaks 50%. The larger the tensile fatigue index, the better the tensile fatigue performance.

[0095] During the tensile fatigue test, the rubber material breaks and fails soon after cracks appear, so tensile fatigue can evaluate the crack initiation state of the rubber material. The data in Table 4 are tensile fatigue indexes.

[0096] From the data in Table 2, it can be seen that different rubber systems have different anti-destructive properties. The crack growth rate of Comparative Example 1-2 is 103% higher than that of Comparative Example 1-1, indicating that the crack growth rate of cis-1,2-butadiene rubber is faster than that of natural rubber. The crack growth rate of Comparative Example 1-3 is 26% higher than that of Comparative Example 1-1, indicating that the fatigue resistance of the styrene-butadiene rubber-natural rubber-cis-1,2-butadiene rubber three-rubber system is between the styrene-butadiene rubber-natural rubber system and the styrene-butadiene rubber-cis-1,2-butadiene rubber system.

[0097] It can be seen from the data in Table 2 that different rubber systems have different tensile fatigue properties. The tensile fatigue index of Comparative Example 1-2 is 52% higher than that of Comparative Example 1-1, indicating that the time for cracks to appear in butadiene rubber is slower than that in natural rubber, that is, compared with natural rubber, butadiene rubber has a better ability to delay crack initiation.

[0098] The crack growth rate of Example 1-1 is 36% lower than that of Comparative Example 1-1, the crack growth rate is greatly reduced, and the anti-destruction performance is improved. The tensile fatigue index of Example 1-1 is 60% higher than that of Comparative Example 1-1, the crack initiation time is greatly delayed, and the anti-destruction performance is improved. The aging retention rate of tensile strength of Example 1-1 is 6% higher than that of Comparative Example 1-1, and the aging retention rate of tensile strength is significantly improved. The aging retention rate of elongation at break of Example 1-1 is 4% higher than that of Comparative Example 1-1, and the aging retention rate of elongation at break is significantly improved. The hysteresis loss factor of Example 1-1 has a slight change of 1% compared with Comparative Example 1-1, and has no obvious effect on rolling resistance. The addition of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide significantly improves the durability and anti-destruction performance of rubber materials.

[0099] From the data in Table 2, it can be seen that the addition of 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine significantly reduces the rolling resistance of the rubber material. The hysteresis loss factor of Example 1-2 is 14% lower than that of Comparative Example 1-1, and the rolling resistance is significantly reduced. 2 When the crack growth rate of Example 1-2 is 28% higher than that of Comparative Example 1-1, the crack growth rate increases, the tensile fatigue index of Example 1-2 is 35% higher than that of Comparative Example 1-1, and the crack initiation time is greatly delayed.

[0100] From the data in Table 2, it can be seen that by adding N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide and 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine at the same time, the anti-damage performance of the rubber material is significantly improved, the rolling resistance is significantly reduced, and the physical property retention rate after aging is high. 2 , the crack growth rate of Example 1-3 is 34% lower than that of Comparative Example 1-1, the crack growth rate is greatly reduced, and the anti-destruction performance is improved. The tensile fatigue index of Example 1-3 is 55% higher than that of Comparative Example 1-1, the crack initiation time is greatly delayed, and the anti-destruction performance is improved. The hysteresis loss factor of Example 1-3 is 11% lower than that of Comparative Example 1-1, and the rolling resistance is significantly reduced. The aging retention rate of the tensile strength of Example 1-3 is 8% higher than that of Comparative Example 1-1, and the aging retention rate of the tensile strength is significantly improved. The aging retention rate of the elongation at break of Example 1-3 is 7% higher than that of Comparative Example 1-1, and the aging retention rate of the elongation at break is significantly improved. Compared with Comparative Example 1-1, the Mooney viscosity of Example 1-3 has a small change of 1%, which has no obvious effect on the processing performance.

[0101] Therefore, when adjusting the formula, in order to obtain the best anti-destruction performance and low rolling resistance performance, hydrazide compounds can be added to the formula system of low rolling resistance modifier, which can significantly improve the anti-destruction performance of the rubber composition, improve the retention rate of physical properties after aging, and achieve low rolling resistance and good processing performance at the same time without reducing the physical and mechanical properties.

[0102] From the data in Table 2, it can be seen that in the formula system of styrene-butadiene rubber / butadiene rubber, the addition of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide can also significantly improve the anti-destructive performance of the rubber material. 2, the crack growth rate of Example 1-4 is 26% lower than that of Comparative Example 1-2, and the crack growth rate is greatly reduced. At the same time, the tensile fatigue index of Example 1-4 is 32% higher than that of Comparative Example 1-2, the crack initiation time is greatly delayed, and the anti-destruction performance is improved. Improved anti-destruction performance. Compared with Comparative Example 1-2, the Mooney viscosity of Example 1-4 is unchanged, and has no effect on processing performance. The hysteresis loss factor of Example 1-4 is unchanged compared with Comparative Example 1-2, and has no effect on rolling resistance. The aging retention rates of tensile strength and elongation at break of Example 1-4 are increased by 10% and 9% respectively compared with Comparative Example 1-2. After aging, the physical property retention rate of the rubber material with the addition of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide is significantly increased.

[0103] From the data in Table 2, it can be seen that in the formula system of styrene-butadiene rubber / butadiene rubber / natural rubber, the addition of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide can significantly improve the anti-destructive performance of multi-component complex rubber materials. 2 , the crack growth rate of Example 1-5 is 14% lower than that of Comparative Example 1-3, and the crack growth rate is greatly reduced. At the same time, the tensile fatigue index of Example 1-5 is 29% higher than that of Comparative Example 1-3, the crack initiation time is greatly delayed, and the anti-destruction performance is improved. Improved anti-destruction performance. The MA300 of Example 1-5 is 2% lower than that of Comparative Example 1-3, and the fatigue crack resistance is improved. Compared with Comparative Example 1-3, the Mooney viscosity of Example 1-5 has a small change of 1%, which has no obvious effect on the processing performance. The hysteresis loss factor of Example 1-5 is 5% lower than that of Comparative Example 1-3, and the rolling resistance is significantly reduced. The aging retention rates of tensile strength and elongation at break of Example 1-5 are increased by 10% and 5% respectively compared with Comparative Example 1-3, and the aging retention rate of the physical properties of the rubber material with the addition of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide is significantly increased.

[0104] Therefore, in different formulation systems, including multi-component complex formulation systems with multiple rubbers, adding hydrazide compounds can also improve the compatibility of multi-component complex systems, significantly improve the anti-destruction performance of the rubber composition, significantly improve the physical property retention rate of the rubber composition after aging, and at the same time improve or not significantly improve the rolling resistance, and have good processing performance. When the low rolling resistance modifier tetrazine compound is used in the hydrazide compound formulation system, the anti-destruction performance of the rubber composition is significantly improved, the physical property retention rate after aging is improved, and low rolling resistance and good processing performance are achieved at the same time, without reducing the physical and mechanical properties.

[0105] Example 2

[0106] Table 3 Formula table of comparative example 2-1 and embodiments 2-1 to 2-4

[0107]

[0108] The raw materials used in Comparative Example 2-1 and Examples 2-1 to 2-4 of the present invention are shown in Table 3, all in mass parts. Among them, Examples 2-1 to 2-4 are rubber compositions used in N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthoic acid hydrazide, isophthalic acid dihydrazide, and 3-hydroxy-2-naphthoic acid hydrazide.

[0109] Preparation method of the rubber composition in Table 3: (1) Weigh each raw material according to the weight proportion of the rubber composition in Table 3; (2) SOL5251H, BR9000 and natural rubber are mixed for 30 seconds, hydrazide compounds, protective wax, stearic acid, 6PPD, DPG and Si69 are added and mixed for 90 seconds, HD165MP, N234 and Vivatec700 are added and mixed, zinc oxide is added and mixed at 130°C, the mixing time is 120 seconds at a temperature of 140-150°C, and the debonding temperature is 150°C to obtain material A; (3) Material A is left for 4 hours, cooled, sulfur and CBS are added and mixed, the mixing is performed for 180 seconds, and the debonding temperature is 105°C to obtain the rubber composition.

[0110] The performance test results for Examples 2-1 to 2-4 and Comparative Example 2-1 are shown in Table 4 below:

[0111] Table 4: Comparison of performance results of Examples 2-1 to 2-4 and Comparative Example 1-1

[0112]

[0113] * The test results of the rubber composition are expressed in the form of an index, with the test result of Comparative Example 2-1 being 100.

[0114] The calculation formula is: Example test result = (Example / Comparative Example 2-1)×100.

[0115] a Crack Growth Rate Index @2000J / m 2 :Evaluated by crack extension tester, the data in Table 4 are tearing energy 2000J / m 2 The smaller the exponent, the slower the crack growth rate.

[0116] b1 Tensile strength after aging, b2 Elongation at break after aging: aging temperature is 100℃, aging time is 72 hours, thermal oxygen aging.

[0117] b3Tensile strength aging retention rate = tensile strength after aging / tensile strength before aging. The larger the value, the higher the tensile strength aging retention rate.

[0118] b4 Elongation at break aging retention rate = elongation at break after aging / elongation at break before aging. The larger the value, the higher the elongation at break aging retention rate.

[0119] c Tensile fatigue index: evaluated by a tensile fatigue testing machine. The data in Table 4 are the tensile fatigue times when the sample breaks 50%. The larger the tensile fatigue index, the better the tensile fatigue performance.

[0120] During the tensile fatigue test, the rubber material breaks and fails soon after cracks appear, so tensile fatigue can evaluate the crack initiation state of the rubber material. The data in Table 4 are tensile fatigue indexes.

[0121] From the data in Table 4, it can be seen that compared with Comparative Example 2-1, the crack growth rates of Example 2-1 and Example 2-2 are reduced by 8% and 19%, respectively, the crack growth rate is greatly reduced, and the anti-destruction performance is improved. As the amount of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide added increases, the crack growth rate decreases and the anti-destruction performance is improved. Compared with Comparative Example 2-1, the tensile fatigue index of Example 2-1 and Example 2-2 is 60% and 93% higher, respectively, the tensile fatigue performance is significantly improved, and the anti-destruction performance is improved. The aging retention rate of tensile strength of Example 2-2 is 8% higher than that of Comparative Example 2-1, and the aging retention rate of tensile strength is significantly improved. The aging retention rate of elongation at break of Example 2-2 is 7% higher than that of Comparative Example 2-1, and the aging retention rate of elongation at break is significantly improved. Compared with Comparative Example 2-1, the hysteresis loss factor of Example 2-2 has a small change of 1%, which has no obvious effect on rolling resistance. The addition of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide can significantly improve the durability and damage resistance of rubber materials.

[0122] Compared with Comparative Example 2-1, the crack growth rates of Example 2-3 and Example 2-4 are reduced by 8% and 11%, respectively, the crack growth rate is reduced, and the anti-destruction performance is improved. Compared with Comparative Example 2-1, the tensile fatigue index of Example 2-3 and Example 2-4 is 24% and 20% higher, respectively, the tensile fatigue performance is significantly improved, and the anti-destruction performance is improved. The aging retention rate of the tensile strength of Example 2-3 is 3% higher than that of Comparative Example 2-1, and the aging retention rate of the tensile strength is improved. The aging retention rate of the tensile strength of Example 2-4 is 3% higher than that of Comparative Example 2-1, and the aging retention rate of the tensile strength is improved. With the addition of isophthalic acid dihydrazide and 3-hydroxy-2-naphthoic acid hydrazide, the durability and anti-destruction performance of the rubber material are significantly improved.

[0123] Therefore, in the formulation system of low-filler fillers, adding hydrazide compounds can also significantly improve the anti-destruction performance of the rubber composition, and the physical property retention rate of the rubber composition after aging is significantly improved, while the rolling resistance is not significantly improved, and it has good processing performance without reducing the physical and mechanical properties.

[0124] Example 3

[0125] Table 5 Comparative Example 3-1 and Examples 3-1 to 3-2 Formulations

[0126] Raw materials (unit: kg) Comparative Example 3-1 Example 3-1 Example 3-2 SOL5251H 70 70 70 Natural rubber (STR20) 30 30 30 HD165MP 90 90 90 N375 7.2 7.2 7.2 Si69 7.2 7.2 7.2 Vivatec700 40 40 40 6PPD 2 2 2 TMQ 1 1 1 Protective wax 1.5 1.5 1.5 Stearic acid 2 2 2 Zinc Oxide 2 2 2 DPG 1.5 1.5 1.5 N'-(1,3-Dimethylbutylidene)-3-hydroxy-2-naphthohydrazide 1 Isophthalic acid dihydrazide 0.5 CBS 2 2 2 sulfur 1 1 1

[0127] The raw materials used in Comparative Example 3-1 and Examples 3-1 to 3-2 of the present invention are shown in Table 5, all in mass parts. Among them, Examples 3-1 to 3-2 are rubber compositions using N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide and isophthalic acid dihydrazide.

[0128] Preparation method of the rubber composition in Table 5: (1) Weigh each raw material according to the weight proportion of the rubber composition in Table 5; (2) SOL5251H, BR9000 and natural rubber are mixed for 30 seconds, hydrazide compounds, protective wax, stearic acid, 6PPD, DPG and Si69 are added and mixed for 90 seconds, HD165MP, N234 and Vivatec700 are added and mixed, zinc oxide is added and mixed at 135°C, the mixing time is 120 seconds at a temperature of 140-150°C, and the debonding temperature is 150°C to obtain material A; (3) Material A is allowed to stand for 4 hours, and after cooling, sulfur and CBS are added and mixed, the mixing is performed for 180 seconds, and the debonding temperature is 105°C to obtain the rubber composition.

[0129] The performance test results for Examples 3-1 to 3-2 and Comparative Example 3-1 are shown in Table 6 below:

[0130] Table 6: Comparison of performance results of Examples 3-1 to 3-2 and Comparative Example 3-1

[0131] Test Item* Comparative Example 3-1 Example 3-1 Example 3-2 Mooney viscosity 100 103 107 Mooney Scorch 100 106 96 hardness 100 104 105 MA100 100 107 110 MA300 100 101 102 Tensile Strength 100 102 105 Elongation at break 100 99 100 Hysteresis loss factor 100 101 99 <![CDATA[ a Crack Growth Rate Index @2000J / m 2 ]]> 100 68 74 <![CDATA[ b1 Tensile strength after aging]]> 100 108 107 <![CDATA[ b2 Elongation at break after aging]]> 100 104 102 <![CDATA[ b3 Tensile strength aging retention rate]]> 100 106 102 <![CDATA[ b4 Elongation at break Aging retention rate]]> 100 105 102 <![CDATA[ c Tensile fatigue index]]> 100 145 123

[0132] * The test results of the rubber composition are expressed in the form of an index, with the test result of Comparative Example 3-1 being 100.

[0133] The calculation formula is: Example test result = (Example / Comparative Example 3-1)×100.

[0134] a Crack Growth Rate Index @2000J / m 2 :Evaluated by crack extension tester, the data in Table 6 are tearing energy 2000J / m 2The smaller the exponent, the slower the crack growth rate.

[0135] b1 Tensile strength after aging, b2 Elongation at break after aging: aging temperature is 100℃, aging time is 72 hours, thermal oxygen aging.

[0136] b3 Tensile strength aging retention rate = tensile strength after aging / tensile strength before aging. The larger the value, the higher the tensile strength aging retention rate.

[0137] b4 Elongation at break aging retention rate = elongation at break after aging / elongation at break before aging. The larger the value, the higher the elongation at break aging retention rate.

[0138] c Tensile fatigue index: evaluated by a tensile fatigue testing machine. The data in Table 6 are the tensile fatigue times when the sample breaks 50%. The larger the tensile fatigue index, the better the tensile fatigue performance.

[0139] During the tensile fatigue test, the rubber material breaks and fails soon after cracks appear, so tensile fatigue can evaluate the crack initiation state of the rubber material. The data in Table 6 are tensile fatigue indexes.

[0140] From the data in Table 6, it can be seen that compared with Comparative Example 3-1, the crack growth rates of Example 3-1 and Example 3-2 are reduced by 32% and 26%, respectively, the crack growth rate is greatly reduced, and the anti-destruction performance is improved. Compared with Comparative Example 3-1, the tensile fatigue index of Example 3-1 and Example 3-2 is 45% and 23% higher, respectively, the tensile fatigue performance is significantly improved, and the anti-destruction performance is improved. The aging retention rate of the tensile strength of Example 3-1 is 6% higher than that of Comparative Example 3-1, and the aging retention rate of the tensile strength is significantly improved. The aging retention rate of the elongation at break of Example 3-2 is 2% higher than that of Comparative Example 3-1, and the aging retention rate of the tensile strength is also improved. Compared with Comparative Example 3-1, the hysteresis loss factor of Example 3-1 has a small change of 1%, which has no obvious effect on rolling resistance. The addition of N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide and isophthalic acid dihydrazide significantly improves the durability and anti-destruction performance of the rubber material.

[0141] Therefore, adding hydrazide compounds to the formulation system of highly filled silica can also significantly improve the anti-destruction performance of the rubber composition. The physical property retention rate of the rubber composition after aging is significantly improved, while the rolling resistance is not significantly improved. It has good processing performance without reducing the physical and mechanical properties.

[0142] The above test results show that the addition of hydrazide compounds improves the fatigue crack resistance. This is mainly because hydrazide compounds can modify rubber, thereby improving the compatibility of the rubber system in the formula system, improving the microscopic phase separation of rubber, and slowing down crack initiation. On the other hand, after hydrazide compounds are complexed with zinc oxide, they stabilize the sulfur cross-linking bonds and improve the rubber system's ability to resist crack propagation.

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A rubber composition for a tire crown component, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of diene rubber, 0.3-3 parts of hydrazide compound, 40-160 parts of reinforcing filler, 0-1.5 parts of low rolling resistance modifier, 2-18 parts of silane coupling agent, 0.1-4.5 parts of vulcanization accelerator, 0.1-4.5 parts of vulcanizing agent, 1-6 parts of antioxidant, 0.1-5 parts of vulcanization activator, 0-5 parts of processing aid, 0-80 parts of resin and plasticizer, 0.2-5 parts of stearic acid, 1-9 parts of zinc oxide, 0.5-5 parts of protective wax and 0.1-4.5 parts of sulfur; The structure of the hydrazide compound is: R1-CO-NH-NH2(1) NH2-NH-CO-R2-CO-NH-NH2(2) R3-CO-NH-N=R4 (3) Wherein, R1, R2, R3, R4 are independently selected from: an aromatic hydrocarbon group having 6 to 30 carbon atoms or an alkane group having 6 to 30 carbon atoms; the aromatic hydrocarbon is arbitrarily substituted by an alkyl group, a hydroxyl group or an amino group having 1 to 20 carbon atoms; The hydrazide compound is used to stabilize the sulfur cross-linking bond after complexing with zinc oxide, thereby improving fatigue crack resistance, delaying crack initiation, reducing crack propagation rate, and improving physical property retention rate after aging; The low rolling resistance modifier has a structure of: Wherein X1 and X2 represent a heterocyclic group which may have a substituent, and the substituent is an alkyl group, an aralkyl group, an aryl group or a heterocyclic group.

2. The rubber composition for a tire crown component according to claim 1, characterized in that: The diene rubber is any one or more combinations of modified or unmodified natural rubber, polyisoprene rubber, polybutadiene rubber, butadiene rubber, styrene-butadiene copolymer rubber, ethylene-propylene-diene monomer copolymer, styrene-isoprene-styrene terblock copolymer rubber, and styrene-butadiene-styrene terblock copolymer rubber.

3. The rubber composition for a tire crown component according to claim 2, characterized in that: The diene rubber is any one or more combinations of modified or unmodified styrene-butadiene copolymer rubber and polybutadiene rubber, and the amount of the styrene-butadiene copolymer rubber and polybutadiene rubber is 50-100 parts.

4. The rubber composition for a tire crown component according to claim 2, characterized in that: The diene rubber is a combination of any one or more of modified or unmodified natural rubber and polyisoprene rubber, and the amount of the natural rubber and polyisoprene rubber is 0-50 parts.

5. The rubber composition for a tire crown component according to claim 1, characterized in that: The hydrazide compound is a combination of any one or more of adipic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, suberic acid dihydrazide, sebacic acid dihydrazide, dodecanoic acid dihydrazide, benzoic acid hydrazide, naphthoic acid hydrazide, propionic acid hydrazide, caprylic acid hydrazide, stearic acid hydrazide, caproic acid hydrazide, capric acid hydrazide, oleic acid hydrazide, lauric acid hydrazide, palmitic acid hydrazide, N'-(1,3-dimethylbutylene)-3-hydroxy-2-naphthohydrazide, 2-hydroxy-naphthoic acid hydrazide, 3-hydroxy-2-naphthoic acid hydrazide, and 2-hydroxy-benzoic acid hydrazide, and the amount of the hydrazide compound is 0.3-1.5 parts.

6. The rubber composition for a tire crown component according to claim 1, characterized in that: The reinforcing filler is a mixture of one or more of modified or unmodified carbon black, acetylene black, white carbon black, carbon nanotubes, graphite, and graphene. The amount of white carbon black in the reinforcing filler is 40-150 parts, and the amount of carbon black is 1-40 parts.

7. The rubber composition for a tire crown component according to claim 1, characterized in that: The low rolling resistance modifier is a tetrazine compound. Further, the low rolling resistance modifier is a combination of any one or more of 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine, 3,6-bis(3-pyridyl)-1,2,4,5-tetrazine, and 3,6-bis(4-pyridyl)-1,2,4,5-tetrazine. The amount of the low rolling resistance modifier is 0.3-1.2 parts.

8. The rubber composition for a tire crown component according to claim 1, characterized in that: The coupling agent is a combination of any one or more of bis-[3-(triethoxysilyl)propyl]-tetrasulfide, bis-[3-(triethoxysilyl)propyl]-disulfide, 3-octanoylthio-1-propyltriethoxysilane, γ-mercaptopropylethoxybis-(propyl-hexaethoxysiloxane) and mercaptoalkoxy-ethoxy or methoxysilane, and the amount of the coupling agent is 3-16 parts.

9. A method for preparing a rubber composition, comprising the steps of: Step (1) weighing various raw materials: the raw materials include diene rubber, hydrazide compound, reinforcing filler, low rolling resistance modifier, silane coupling agent, vulcanization accelerator, vulcanizing agent, antioxidant, vulcanization activator, processing aid, resin and plasticizer, stearic acid, zinc oxide, protective wax and sulfur; Step (2) mixing diene rubber and hydrazide compound, low rolling resistance modifier, antioxidant, silane coupling agent, processing aid, etc. for 30-200 seconds, mixing reinforcing filler, silane coupling agent and plasticizer and reacting at 80-160° C. for 30-200 seconds, adding vulcanization activator at 80-140° C. and mixing at 120-180° C. for 60-300 seconds, and cooling to obtain material A; Step (3) adding a vulcanizing agent and a vulcanization accelerator to material A, mixing and discharging the mixture, and then subjecting the mixture to a vulcanization reaction at a vulcanization temperature of 130-180° C. and a vulcanization time of 10-200 min to obtain a rubber composition for a tire crown component.

10. A tire, characterized in that: The crown component of the tire is prepared from the rubber composition for the crown component of the tire according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composition based on natural rubber and a reinforcing inorganic filler comprising a dihydrazide

    CN102257056A

  • Composition based on natural rubber and carbon black comprising hydrazide, hydrazone and polyamine

    CN103261300A

  • Rubber composition

    CN104558713A

  • All-steel radial tire tread rubber and preparation method thereof

    CN111592695A

  • Low-heat-generation and high-thermal-conductivity tire base rubber composition and mixing method thereof and tire

    CN113652012A

Cited By

  • Antibacterial bioactive glass composite material for skull defect repair and preparation method thereof

    CN121819031A

  • Antibacterial bioactive glass composite for cranioplasty and method of making same

    CN121819031B